The Role of the Oral Microbiota in the Etiopathogenesis of Oral Squamous Cell Carcinoma - Vyhnalova, Tereza; Danek, Zdenek; Gachova, Daniela; Linhartova, Petra Borilova (Microorganisms, 2021)
Dysbiosis in the oral environment may play a role in the etiopathogenesis of oral squamous cell carcinoma (OSCC). This review aims to summarize the current knowledge about the association of oral microbiota with OSCC and to describe possible etiopathogenetic mechanisms involved in processes of OSCC development and progression. Association studies included in this review were designed as case-control/case studies, analyzing the bacteriome, mycobiome, and virome from saliva, oral rinses, oral mucosal swabs, or oral mucosal tissue samples (deep and superficial) and comparing the results in healthy individuals to those with OSCC and/or with premalignant lesions. Changes in relative abundances of specific bacteria (e.g., Porphyromonas gingivalis, Fusobacterium nucleatum, Streptococcus sp.) and fungi (especially Candida sp.) were associated with OSCC. Viruses can also play a role; while the results of studies investigating the role of human papillomavirus in OSCC development are controversial, Epstein-Barr virus was positively correlated with OSCC. The oral microbiota has been linked to tumorigenesis through a variety of mechanisms, including the stimulation of cell proliferation, tumor invasiveness, angiogenesis, inhibition of cell apoptosis, induction of chronic inflammation, or production of oncometabolites. We also advocate for the necessity of performing a complex analysis of the microbiome in further studies and of standardizing the sampling procedures by establishing guidelines to support future meta-analyses.
Keywords: oral carcinogenesis; oral squamous cell carcinoma; tumor microenvironment; oral cancer; Candida sp.; Porphyromonas gingivalis; oral microbiome